2020
DOI: 10.1038/s41598-020-57940-9
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B and I inhibits colon cancer growth by targeting the Notch signaling pathway

Abstract: cancer stem cells (cScs) have the ability to self-renew and induce drug resistance and recurrence in colorectal cancer (cRc). As current chemotherapy doesn't eliminate cScs completely, there is a need to identify novel agents to target them. We investigated the effects of cucurbitacin B (C-B) or I (C-I), a natural compound that exists in edible plants (bitter melons, cucumbers, pumpkins and zucchini), against cRc. c-B or c-i inhibited proliferation, clonogenicity, induced G 2 /M cell-cycle arrest and caspase-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 59 publications
0
36
1
Order By: Relevance
“…For example, CuB tablets could be used for the treatment of chronic hepatitis in China [13]. It is noteworthy that the antitumor activity of CuB was widely reported in a variety of cancers, including liver cancer, lung cancer, skin cancer, colorectal cancer, breast cancer [14], laryngeal squamous cell carcinoma [15], osteosarcoma [16] and pancreatic cancer [17]. Previous studies have shown that the antitumor effects can be enhanced further when CuB is combined with curcumin in hepatoma cells [18] and also when CuB is combined with gefitinib in human colorectal cancer cell [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, CuB tablets could be used for the treatment of chronic hepatitis in China [13]. It is noteworthy that the antitumor activity of CuB was widely reported in a variety of cancers, including liver cancer, lung cancer, skin cancer, colorectal cancer, breast cancer [14], laryngeal squamous cell carcinoma [15], osteosarcoma [16] and pancreatic cancer [17]. Previous studies have shown that the antitumor effects can be enhanced further when CuB is combined with curcumin in hepatoma cells [18] and also when CuB is combined with gefitinib in human colorectal cancer cell [19].…”
Section: Introductionmentioning
confidence: 99%
“…The blockade of PD-L1 increased FABP4 expression in tissue-resident memory T (Trm) cells, promoting lipid uptake by Trm cells [ 50 ]. Previous reports indicate that the hedgehog signaling pathway might affect the recurrence of COAD patients [ 51 ]. Dandawate et al reported that the Notch signaling pathway involved regulating colon cancer cells’ proliferation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that the hedgehog signaling pathway might affect the recurrence of COAD patients [ 51 ]. Dandawate et al reported that the Notch signaling pathway involved regulating colon cancer cells’ proliferation [ 51 ]. Our results are consistent with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Also, tumor growth can inhibits by CuB in a dose-dependent way in Hep-2 cells and in vivo researches in a mouse xenograft model. 68 23, 24-Dihydrocucurbitacin B, found to inhibit the proliferation of HeLa, Bcap37, SMMC-7721, K562 SW620 and MCF-7, human cancer cell lines and induce apoptosis in Bcap37 human breast cancer cell line. DHCB induces Bcap37 apoptosis through mitochondrial dependent pathway and stopping induction of G2/M phase in cell-cycle as well.…”
Section: Apoptosis and Cell Cycle Arrestmentioning
confidence: 99%